Improving Adherence to Weight‐Loss Medication (Liraglutide 3.0 mg) Using Mobile Phone Text Messaging and Healthcare Professional Support. Issue 10 (9th September 2020) - Li, Ang; Cunich, Michelle; Fuller, Nicholas; Purcell, Katrina; Flynn, Allanah; Caterson, Ian
Abstract : Background: Adherence to weight‐loss medication is suboptimal, leading to poor health outcomes. Short message service (SMS) can potentially improve adherence. Methods: A total of 3, 994 participants with overweight or obesity in Australia receiving Saxenda® (liraglutide 3.0 mg) were enrolled from September 1, 2017, to February 28, 2018, through doctors, pharmacists, or websites and were randomly assigned to receive none, three, or five SMS per week. Participants were additionally offered a face‐to‐face consultation with a diabetes educator or a call from a dietitian. Medication adherence was measured as whether the total scripts claimed were at least as many as the total claims expected by March 31, 2018, and was modeled adjusting for age, sex, baseline BMI, residential region, enrolment channel, the total number of SMS, and additional patient support. Results: Participants receiving five SMS (OR, 6.25; 95% CI: 4.28‐9.12) had greater adherence than those receiving three SMS (OR, 3.67; 95% CI: 2.67‐5.03) or zero SMS per week. The effectiveness of SMS on adherence decreased as participants received more SMS over time. Moreover, the odds of adhering to liraglutide were higher for participants enrolled with pharmacists compared with those enrolled with doctors (OR, 2.28; 95% CI: 1.82‐2.86) and for participants who received a face‐to‐face consultation (OR, 3.10; 95% CI: 1.82‐5.29) or a call (OR, 1.31; 95% CI: 1.02‐1.68) compared with those who received no extra support. Conclusions: Integration of SMS into routine clinical practice should consider not only the frequency and content of reminders but also additional patient support to achieve higher and more sustained adherence to medication and health behavior changes.